Exploration in Northern Kutch - Jоshi, Jagat Pati (1966)
1. The Problem and its Approach; 2. Situation and Physical Features; 3. Previous Explorations and Excavations; 4. Present Work: Objective and Scope; 5. Explored Harappan Sites (Surkotda, Kerasi, Pabumath, Lakhapar, Jhangar, Kotada, Pirwada Khetar, Kotada Bhadli, Khari ka Khanda); 6. In the Sequel; 7. Acknowledgements; Harappan Sites in Kutch.